Academic Achievement in Physics-Chemistry: The Predictive Effect of Attitudes and Reasoning Abilities - Vilia, Paulo N.; Candeias, Adelinda A.; Neto, António S.; Franco, Maria Da Glória S.; Melo, Madalena (Frontiers in Psychology, 2017)
Science education plays a critical role as political priority due to its fundamental importance in engaging students to pursue technological careers considered essential in modern societies, in order to face scientific development challenges. High-level achievement on science education and positive attitudes toward science constitutes a crucial challenge for formal education. Several studies indicate close relationships between students´ attitudes, cognitive abilities and academic achievement. The main purpose of this study is to analyze the impact of student’s attitudes towards the school discipline of Physics and Chemistry and their reasoning abilities on academic achievement on that school subject, among Portuguese 9th grade students using the data collected during the Project Academic Performance and Development: a longitudinal study on the effects of school transitions in Portuguese students (PTDC/CPE-CED/104884/2008). The participants were 470 students (267 girls– 56,8% and 203 boys – 43,2%), aged 14 to 16 years old (µ=14.3 ± .58). The attitude data were collected using the Attitude towards Physics-Chemistry Questionnaire (ATPCQ) and, the Reasoning Test Battery (RTB) was used to assess the students reasoning abilities. Achievement was measured using the students’ quarterly (nine-week) grades in the physics and chemistry subject The relationships between the attitude dimensions towards Physics-Chemistry and the reasoning dimensions and achievement in each of the three school terms were assessed by multiple regression stepwise analyses and standardized regression coefficients (β), calculated with IBM SPSS Statistics 21 software. Both variables studied proved to be significant predictor variables of school achievement. The models obtained from the use of both variables were always stronger accounting for higher proportions of student’s grade variations. The results show that ATPCQ and RTB had a significantly positive relationship with student’s achievement in Physics-Chemistry, indicating that both attitudinal and cognitive variables should be taken into account on science education as well as in educative intervention.